ANALYSIS OF STEEL COLUMN MODELING IN CONSTRUCTION FOR BOILER WAREHOUSE EXPANSION BASED ON SAP SOFTWARE - Hermansyah Hermansyah; Mahpuja Narti Simatupang; Hutauruk Hutauruk; Denny Meisandi; Habib Satria; Indri Dayana (Indonesian Journal of Engineering and Science, 2023)
The superstructure is all components that are above the ground. The function of the superstructure is as a support for the building with an upward elongated shape, such as frames, trusses, beams, and columns. The column is a vertical compression member of the structural frame that carries the load from the beam. The construction of this warehouse is located in Tanjung Morawa using IWF steel columns. In this study, the strength of the steel columns was analyzed by modeling using SAP 2000 V.14 and manually calculated on the F portal using the LRFD (Load and Resistance Factor Design) method. The research method uses primary data, namely direct field observations in the form of interviews, and secondary data, namely data taken from the contractor in the form of pictures or from books, previous research, and so on. Based on the results of structural modeling using SAP 2000 V.14, it was concluded that the building is safe; on manual analysis on the F portal, it can be concluded that the steel columns WF-300×150×9×13 and WF-350×175×7×11 are capable of carrying factored compressive loads.